Using Stakeholder Preferences to Identify Optimal Land Use Configurations - Kaim, Andrea; Strauch, Michael; Volk, Martin (Frontiers in Water, 2020)
One way to solve multi-objective spatial land use allocation problems is to calculate a set of Pareto-optimal solutions and include stakeholder preferences after the optimization process. There are various land use allocation studies that identify the Pareto frontier (i.e. trade-off curve) but, to our knowledge, for the majority of them it remains open which solutions should be implemented or are preferred by stakeholders. One reason could be that Pareto-optimal solutions, due to their multi-dimensionality, are difficult to communicate. To fill this gap, we give an example using the results of a multi-objective agricultural land use allocation problem that maximizes four biophysical objectives: agricultural production, water quality, water quantity and biodiversity in the Lossa River Basin in Central Germany. We conducted expert interviews with eleven local stakeholders from different backgrounds, e.g. water experts, nature conservationists, farmers, etc. In addition to providing information about the case study area, we visualized the trade-offs between the different objectives using parallel coordinates plots that allowed the stakeholders to browse through the optimal solutions. Based on this information, the stakeholders set weights for each of the objectives by applying the Analytic Hierarchy Process (AHP). With these weights, we selected the preferred solutions from the Pareto-optimal set. The results show that overall, stakeholders clearly ranked water quality first, then biodiversity, water quantity and agricultural production. The corresponding land use maps show a huge difference in land management (e.g. less application of fertilizer, more linear elements, conservation tillage) for the preferred solutions compared to the current status. The method presented in this study can help decision makers finding land use and land management strategies based on both, biophysical modelling results and stakeholder expertise and shows a way how multi-objective optimization results can be communicated and used for an information-based decision-making process.